Spatial network structure and influencing factors of carbon emission intensity in Guangdong-Hong Kong-Macao greater bay area - Wei, Heng; Zheng, Chaohui (Frontiers in Environmental Science, 2024)
To expedite progress towards China's ambitious dual-carbon objectives and to achieve energy conservation and emission reduction, this study employs spatial autocorrelation analysis, Social Network Analysis (SNA), and Quadratic Assignment Procedure (QAP) methodologies. Accordingly, utilizing carbon emission and socio-economic data between 2000 and 2020 from the Guangdong-Hong Kong-Macao Great Bay Area (GBA), the study seeks to explore spatial correlation structure characteristics and influencing factors of carbon emission intensity in GBA. It explores how the overall spatial correlation network of carbon emissions exhibits a pattern of periodic fluctuations, marked by a network structure of varying cohesion among cities. The results shows that: 1)From 2000 to 2020, the overall spatial network of carbon emissions in the GBA exhibited a cyclical fluctuation trend, with a loosely structured network between cities, offering significant opportunities for spatial optimization.2) Analysis of individual network structure indicators and block model results uncovers a pronounced "core-periphery" distribution in this spatial correlation network. in this framework, economically robust cities such as Hong Kong and Macao occupy central positions in the network, whereas less economically developed cities such as Huizhou and Jiangmen are situated on the periphery. Key cities such as Guangzhou and Shenzhen assume a critical "mediator" role in this context. 3) The concluding QAP analysis identifies six categories of differential factors-namely geographic spatial proximity, economic development level, urbanization rate, industrial configuration, level of technological innovation, and environmental protection efforts-as having significant effects. Among them, economic and urban development, industrial structure, and the intensity of environmental protection efforts have a significantly positive impact on spatial relevance. The insights garnered from this research are instrumental for cities in the GBA to define their specific roles in emission reduction and to set targets for low-carbon development.